Using coherent processing algorithms for direction finding of UAV acoustic signals - Kartashov, V.М.; Rybnykov, M.V. (Radiotekhnika, 2023)
Small UAVs are often used in a group, since their signals are highly correlated, their resolution is reduced when using non-coherent processing. The article analyzes the well-known methods of coherent processing of acoustic signals in order to increase the resolution in the direction finding of signals with a high degree of correlation. Obtaining qualitative indicators of the analyzed algorithms was carried out by the method of statistical computer modeling in the Matlab environment. Based on the simulation results, it is shown that coherent signal processing methods are the most stable in conditions of low signal-to-noise ratios, while non-coherent ones show the best results in the region of high signal-to-noise ratio, while coherent algorithms can potentially distinguish more targets. the WAVES coherent algorithm performs better in the high signal-to-noise ratio region, but loses to the CSSM algorithm in the low signal-to-noise region. To increase the efficiency of coherent processing of multipath signals, it applies spatial filtering of the inputsignal.